(untitled) (Health Renaissance, 2014)
Intracranial germinomas typically occur in the suprasellar, pineal, and other locations. Pineal germinoma presenting with Parinaud’s Syndrome is a group of abnormalities of eye movement and pupil dysfunction. It is a rare tumor and its clinical and imaging features can help clinicians in the management of these lesions. DOI: http://dx.doi.org/10.3126/hren.v11i3.9653 Health Renaissance 2013;11(3):276-278